2019
DOI: 10.2134/jeq2018.10.0374
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Biochar and Manure Applications on Soil Carbon Dioxide, Methane, and Nitrous Oxide Fluxes from Two Different Soils

Abstract: Although past research suggested that biochar has the potential to mitigate the emission of greenhouse gases (GHGs), studies investigating how biochar affects GHG emissions from different soil types under field conditions are limited. Furthermore, limited knowledge exists on how interactions between biochar and manure affect GHG emissions from different soils. This field study, conducted in Brookings, SD, in 2013, measured the soil surface GHG emissions (CO 2 , CH 4 , and N 2 O) from sandy loam (SLsoil) and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 112 publications
4
29
1
Order By: Relevance
“…The lack of effect of N and S fertilization rates on CH 4 fluxes in this study was attributed to the similar soil moisture among treatments. Several studies reported no significant effect of N fertilizer rate on soil CH 4 fluxes compared with the control from bioenergy crops in the dryland cropping system (Abagandura, Chintala, et al, 2019; Li et al, 2019; Mbonimpa et al, 2015). Management practices usually have little effect on CH 4 flux in the upland agricultural soils, as reported in our previous studies (e.g., Abagandura, Şentürklü, et al, 2019; Ozlu & Kumar, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of effect of N and S fertilization rates on CH 4 fluxes in this study was attributed to the similar soil moisture among treatments. Several studies reported no significant effect of N fertilizer rate on soil CH 4 fluxes compared with the control from bioenergy crops in the dryland cropping system (Abagandura, Chintala, et al, 2019; Li et al, 2019; Mbonimpa et al, 2015). Management practices usually have little effect on CH 4 flux in the upland agricultural soils, as reported in our previous studies (e.g., Abagandura, Şentürklü, et al, 2019; Ozlu & Kumar, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Release or uptake of CH 4 depends on the microbes present in the soil. The anaerobic microbes release CH 4 and increase these fluxes, while aerobic microbes uptake CH 4 , and result in negative flux (Abagandura, Chintala, et al, 2019). Higher amounts of crop residues (senesced leaves of carinata) at the maturity stage, in combination with moisture and higher temperature, might have triggered the decomposition process, which is the substrate for CH 4 production (Ding et al, 2004).…”
Section: Daily and Seasonal Ghg Fluxesmentioning
confidence: 99%
“…An ICLS can be beneficial in mitigating soil GHG emissions such CO 2 , N 2 O, and CH 4 . The CO 2 emissions are directly influenced by the quantity of C sequestered in the soil (Abagandura, Chintala, Sandhu, Kumar, & Schumacher, 2019a; Alluvione, Bertora, Zavattaro, & Grignani, 2010). The equilibrium of soil C inputs and losses is regulated by addition of cover crop (CC) residues in the soil and decomposition of soil organic matter (SOM).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of biochar on N 2 O emissions remain conflicting, ranging from stimulation ( Lin et al., 2017 ), and reduction ( Abagandura et al., 2019 ). In our study, Azolla + biochar significantly reduced the cumulative N 2 O emission before 63 DAT compared with NPK (97.1%), NPK + biochar (83.0%), and Azolla (86.1%) ( Figure 2 a, Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the shortcomings of either inorganic and/or organic fertilizers, and biochar use in lowland rice paddies as highlighted above, coapplications of inorganic and/or organic fertilizers and biochar amendments, though with differing effects, has been proposed as a suitable practice to achieve sustainable soil health, yield production, and GHG emissions mitigation (Rahman et al, 2020). For example, Abagandura et al (2019) revealed a reduction in cumulative N 2 O fluxes from a sandy loam soil amended with plant-based biochar plus dairy manure, attributed to improved aeration and a subsequent reduction in denitrification, and no significant effects on the cumulative. CH 4 fluxes, partly due similar soil water contents among treatments.…”
Section: Introductionmentioning
confidence: 99%